Performance Optimization of Microvalves Based on a Microhole Array for Microfluidic Chips - Cuimin Sun; Hui You; Yang Xie; Ronald X. Xu (Journal of Analytical Methods in Chemistry)
A microfluidic chip with a microvalve based on a microhole array is proposed in this paper for the POCT of tumor marker proteins. In order to control the biochemical reaction time accurately and obtain a higher testing sensitivity, the parameters of the microhole array are optimized basing on the investigation of the effects of the variation of those parameters on the fluid rate and the residual liquid value in the microvalve region. By conducting liquid flow experiments using microvalves based on microhole arrays with varying microstructural parameters, the residual rate of reaction products is demonstrated to be proportional to the depth and diameter of the microholes and inversely proportional to the distance between the microhole centers. A comprehensive analysis indicates that a microhole depth of 95 μm, a microhole diameter of 230 μm, and a distance between microhole centers of 250 μm not only ensure a sufficiently long delay time, but also reduce the residual rate of reaction products, thereby providing an optimum microvalve performance that maximizes the detection efficiency and accuracy of microfluidic chips.